Kyrgyz Republic : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2000)
The paper describes recent macroeconomic and financial developments and highlights a number of important medium- and longer-term policy issues. Empirical estimates of potential output growth for the Kyrgyz economy based on a number of different methodologies are presented. Competitiveness and trade policy, social policy issues, namely poverty alleviation and pension reform, are also taken up for discussion. Developments in the banking system since 1998 are described. Fiscal issues are discussed and also statistical data on economic indices are presented.